Life-Threatening Hemopericardium Associated with Rivaroxaban - Sijan Basnet; Niranjan Tachamo; Biswaraj Tharu; Rashmi Dhital; Sushil Ghimire; Dilli Ram Poudel (Case Reports in Cardiology)
Rivaroxaban is a novel oral anticoagulant used in the treatment of venous thromboembolism. The use of this medication has expanded over the recent years with resultant expansion of side effect profile. We present a case of a 56-year-old female who presented with shortness of breath and chest pain 12 weeks after starting rivaroxaban for left upper extremity deep vein thrombosis. She was later diagnosed with spontaneous hemopericardium requiring pericardial fluid drainage. Rarer side effects like this will be encountered more often with the increasing use of novel oral anticoagulants. The clinicians should be cognizant of this entity among patients with shortness of breath and chest pain for timely diagnosis and intervention.